INTEGRATING MAHABBAH VALUES INTO THE CURRICULUM OF LOVE: A NEW PARADIGM FOR CHARACTER BUILDING (AKHLAKUL KARIMAH) IN ISLAMIC ELEMENTARY SCHOOLS (MADRASAH IBTIDAIYAH) - Ernawati Ernawati; Herlina Herlina; Wiwi Uswatiyah (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Contemporary Islamic education is often trapped in cognitive formalism that ignores the affective dimension, thus failing to form students' characters authentically. This study aims to analyze the strategy for integrating Mahabbah (love) values within the "Love Curriculum" at MIS Nurussa’adah Bogor, identify the emerging sociological obstacles, and evaluate its impact on the formation of students' akhlakul karimah. Using a qualitative approach with a case study design, data were collected through participant observation, in-depth interviews, and documentation. The results indicate that the integration of Mahabbah values is implemented through a systemic strategy including the "sacralization of general subjects," spiritual culture habituation, and humanist pedagogy that positions teachers as murabbi. A critical finding of this study reveals the challenge of "atmospheric dualism," namely the disconnection between dialogic-affective parenting in the madrasah and repressive discipline or emotional neglect at home, which risks triggering value decay. However, the trans-substantial internalization of values is proven to form a settled character (malakah) and function as a resilient "inner shield" for students in facing domestic environmental contradictions. The novelty of this research lies in the reconstruction of the Love Curriculum as a "character oasis" that not only synergizes intellectual and spiritual intelligence but also builds students' moral resilience in the 5.0 era.